2020
DOI: 10.1002/eat.23444
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to a special issue on eating disorders in Asia

Abstract: Objective: It is our pleasure to introduce a special issue of the International Journal of Eating Disorders on eating disorders (EDs) in Asia. Method: We received such a robust response to the special edition that we were able to fill two issues. Contributions focused on seven main themes: (1) prevalence, (2) time trends, (3) healthcare systems, (4) treatment, (5) risk factors, (6) assessment, and (7) orthorexia. Results: New prevalence and time trend data from China, Iran, Singapore, Japan, and Taiwan suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…This could be explained by a large proportion of studies that had been conducted in Asia (40%) with very large sample sizes and much lower rates compared to Western countries, and the broader period studied (1984–2017) with especially lower prevalence rates before 2000 [ 29 ]. That is in contrast to findings described in a previous review in this journal [ 1 ] and to the notion that anorexia nervosa rates in Asian countries have been increasing in recent years and that they currently appear to be comparable to, or even higher than, those in Western countries [ 32 34 ]. In the review by Qian et al [ 29 ], 6 of the 33 studies included had been published in Chinese and so the results were difficult to evaluate.…”
Section: Incidencecontrasting
confidence: 99%
“…This could be explained by a large proportion of studies that had been conducted in Asia (40%) with very large sample sizes and much lower rates compared to Western countries, and the broader period studied (1984–2017) with especially lower prevalence rates before 2000 [ 29 ]. That is in contrast to findings described in a previous review in this journal [ 1 ] and to the notion that anorexia nervosa rates in Asian countries have been increasing in recent years and that they currently appear to be comparable to, or even higher than, those in Western countries [ 32 34 ]. In the review by Qian et al [ 29 ], 6 of the 33 studies included had been published in Chinese and so the results were difficult to evaluate.…”
Section: Incidencecontrasting
confidence: 99%
“…Regarding research productivity by region, in line with the observations from researchers as reported in recent publications (Kim et al., 2021), the majority of publications emanated from researchers based in Europe and Northern America. This is unsurprising, as EDs have a long research history in Western countries (e.g., self‐starvation; van Deth & Vandereycken, 1994) and were once considered as Western culture‐bound syndromes (Lee, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…And, based on the cultural perspective of EDs, a significant emphasis on thinness is especially pervasive in Western societies (Grogan, 2016). However, this Western preponderance of publications may hinder the understandings of EDs from a global perspective, as the current findings of EDs based on Western eating habits may only partly paint the global phenomenology and burden of EDs (Kim et al., 2021). Notably, the proportion of publications from Eastern & South‐Eastern Asia increased from 8% in 2001–2010% to 9% in 2011–2020, though, the growth is not considerable, as there has been evidence demonstrating a rapid rise of EDs in Asia which houses the largest population (Pike & Dunne, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies suggest that EDs are increasingly common in Asia (Kim et al, 2021) but not much is known about EDs in Malaysia. Recent changes in diet and activity patterns associated with economic development in Malaysia have led to an increase in excess body weight.…”
Section: Discussionmentioning
confidence: 99%